Career burnout : causes and cures - Pines, Ayala; Aronson, Elliot (New York : The Free Press, 1988)
Our purpose in writing this book is to be able to take what we've learned from our research and our workshops and share it with you. It is our hope that this book will not only help you increase your awareness of burnout in general and your own potential for burnout in particular but in addition will help provide you with the orientation and tools to cope successfully with the problem.
Part one : What is burnout? -- Part two : Causes of burnout -- Part three : Cures
Keywords: MANAGEMENT